The construction of colonial identity in the Canadas, 1815-1867 - Turing, JMF (2014)
This thesis examines the construction and contestation of Anglo-Canadian identity from the end of the War of 1812 until Confederation in 1867. It argues that the conflict between English- and French-speakers in the Canadas was by no means inevitable but a function of the institutional and political circumstances of the time. It seeks to complicate the picture of the British in Canada by demonstrating that they were a diverse community of different groups, institutions and religions that only through struggle and the incentives of party politics were able to unify themselves into a single culture. The development of party politics not just coincided with the creation of Anglo-Canadian identity but played a fundamental role in creating it. Through the burgeoning newspaper industry, the Reform and Tory parties spread their ideas of what it meant to be British, loyal and Canadian to a widespread English-speaking audience. Canadian history in this period is better understood not in the traditional dualist framework of British against French but as the complex interactions of many different groups, including the English, the Scots, the Irish Protestants, the Irish Catholics, the Americans and the French-Canadians. The thesis seeks to deconstruct the terms ‘British’ and ‘loyal’. Both terms were appropriated by various individuals and groups seeking to gain benefits by defining themselves as such. Until the early 1830s, attempts were made to include certain classes of French-Canadians within the broader British polity and identity. The 1837 rebellions marked the ‘othering’ of French-Canadians. Meanwhile the Upper Canada rebellions presented an enemy in the United States and a new strain of anti-Americanism, separate to that of the loyalists, was developed. By 1849, the moment of the rebellion losses crisis, the fundamental tenets of the Anglo-Canadian identity had been established: anti-Americanism, a concern about French political influence and a sense of kinship with English speakers across the province of United Canada. These three periods are shown to have played a crucial role in the development of an anglophone identity that encompassed the whole of United Canada.